Hubungan Pemberian ASI Eksklusif Dengan Perkembangan Anak - Hasnaeni, Hasnaeni; Rahmawati, Rahmawati (Madu : Jurnal Kesehatan, 2023)
The growth and development of a child are determined mainly by the amount of breast milk obtained, including energy and other nutrients contained in breast milk. Breast milk is rich in antibodies because it contains proteins for endurance and high amounts of germ killers, so exclusive breastfeeding can reduce the risk of death in infants. This study aimed to determine the relationship of exclusive breastfeeding to the development of children aged 6-24 months at the Bara-baraya Makassar Health Center. The type of research used was observational analytic with a Cross-Sectional approach; the samples taken were babies aged 6-24 months with a total sampling technique—statistical analysis using the Chi-square test with the SPSS program. The results showed a relationship between exclusive breastfeeding and the development of children aged 6-24 months, with a p-value of 0.05. The role of midwives in educating mothers about the benefits of breast milk given exclusively to infants is needed.